Improvement of a sectional cassette-capacitive apparatus for implementing preliminary thermal processing of plant raw materials - Zahorulko, Andrii; Voronenko, Iryna; Bozhydai, Iryna; Tesliuk, Hennadii; Lebedenko, Olesya; Zakharchenko, Ruslan; Kletskov, Oleksandr; Ibaiev, Eldar (Eastern-European Journal of Enterprise Technologies, 2026)
This study investigates processes of preliminary heat treatment of plant raw materials, using the example of heating a fruit and vegetable semi-finished product based on apples, carrots, beets, and elderberries, as well as partial drying of apple slices in an improved apparatus. The task addressed is to improve resource efficiency in implementing preliminary heat treatment of raw materials by improving a sectional cassette-capacitive apparatus. A feature of the improved apparatus is the combination of capacitive and cassette stations on a truck platform, generation of a local heat supply from a film electric heater of the radiant type to eliminate the intermediate heat carrier, networks. The usable heat exchange surface of capacitive stations was increased from 0.98 m2 to 1.47 m2 through engineering by using mixing devices equipped with a heating surface. The multifunctionality of the device is formed by using a capacitive station equipped with a hemispherical perforated bubbler and hermetic covers with Peltier elements. The capacitive station was tested on the kinetics of heating a semi-finished product (40% apple, 25% carrot, 25% beetroot, and 10% elderberry). It was established that the duration of reaching a gentle stationary mode within 55°C was reduced by 240 s (prototype – 360 s). The cassette station was tested on performing a preliminary thermal operation to dry apple slices to a content of 30…35% dry matter. The process is implemented in an improved device for 45…55 min, while convective drying – 70…85 min. Comparison of technical and technological parameters of the improved design with a steamer and a convective dryer shows a decrease in the specific metal capacity from 387 kg/m2 to 330 kg/m2. Total heat consumption for heating 75 kg of polycomponent puree-like plant mass reduced from 21353 kJ to 11309 kJ